Silicon nanohole arrays fabricated by electron beam lithography and reactive ion etching - Lita Rahmasari,; Mohd Faizol Abdullah,; Ahmad Rifqi Md Zain,; Abdul Manaf Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The fabrication of silicon nanohole (SiNH) using a combination of electron beam lithography (EBL) and reactive ion etching (RIE) processes is reported. The optimum exposure dose of EBL process was found to be in the range of 210-240 μC/cm2 due to small enlargement of hole diameter after pattern development process. The anisotropic etching and isotropic etching was achieved at low and high reaction pressures, respectively. As expected, the etching rate increase with time and RF power. A relatively smooth and well-defined NH has been obtained at RF power of 100 W and reaction pressure of 0.08 Torr, which is suitable to be applied for optical waveguide.